2019
DOI: 10.1111/nph.15801
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase and associated lipid mediators modulate rice root architecture

Abstract: Summary Diacylglycerol kinase (DGK) phosphorylates diacylglycerol (DAG) to generate phosphatidic acid (PA), and both DAG and PA are lipid mediators in the cell. Here we show that DGK1 in rice (Oryza sativa) plays important roles in root growth and development. Two independent OsDGK1‐knockout (dgk1) lines exhibited a higher density of lateral roots (LRs) and thinner seminal roots (SRs), whereas OsDGK1‐overexpressing plants displayed a lower LR density and thicker SRs than wild‐type (WT) plants. Overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Studies have demonstrated that signaling enzymes, diacylglycerol kinases (DGKs) play important roles in response to biotic stress by phosphorylating DG to synthesis PA (Fig. 9) and both PA and DG are lipid mediators during physiological process (Yuan et al 2019). Our findings from this study demonstrate that lipid metabolism and signalling possibly involving DG could play a significant role in pathogen resistance in the tolerant soybean cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that signaling enzymes, diacylglycerol kinases (DGKs) play important roles in response to biotic stress by phosphorylating DG to synthesis PA (Fig. 9) and both PA and DG are lipid mediators during physiological process (Yuan et al 2019). Our findings from this study demonstrate that lipid metabolism and signalling possibly involving DG could play a significant role in pathogen resistance in the tolerant soybean cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that signaling enzymes, diacylglycerol kinases (DGKs) play important roles in response to biotic stress by phosphorylating DG to synthesis PA (Fig. 9) and both PA and DG are lipid mediators during physiological process 60 . Our findings from this study demonstrate that lipid metabolism and signalling possibly involving DG could play a significant role in pathogen resistance in the tolerant soybean cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…TaDGK2 and 6 had higher transcript levels in all organ, especially in roots. The closest ortholog to TaDGK2 is OsDGK1 in rice, which is also highly expressed in roots and affects rice lateral root development and seminal root/ crown root growth [16]. The transcripts of TaDGK7 were di cult to detect, both among tissues/organs and under hormone/stress treatment conditions, which might be owing to its exceptionally long fth intron (Fig.…”
Section: Expression and Functional Divergence Of Tadgk Genesmentioning
confidence: 99%
“…In Arabidopsis, AtDGK7 is expressed ubiquitously, especially in owers and young seedlings [7]. OsDGK1 is intensively expressed in roots system, and modulates the growth and development of roots, which is associated with lipid mediators that control rice root architecture [16].…”
Section: Introductionmentioning
confidence: 99%